2013
DOI: 10.3324/haematol.2013.093823
|View full text |Cite
|
Sign up to set email alerts
|

The synergism of MCL1 and glycolysis on pediatric acute lymphoblastic leukemia cell survival and prednisolone resistance

Abstract: In vitro and in vivo resistance to prednisolone are predictive for an adverse prognosis in pediatric precursor B-acute lymphoblastic leukemia. Causes of resistance are still poorly understood. In this study, we observed that prednisolone exposure of prednisolone-sensitive patients' leukemic cells decreased anti-apoptotic MCL1 protein levels by 2.9-fold, while MCL1 protein expression in prednisolone-resistant leukemic patients' cells was unaffected (P<0.01). Locked nucleic acid oligonucleotides directed against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Glycolysis is critical in childhood ALL. Several pre‐clinical studies showed that aerobic glycolysis inhibitors (Hulleman et al , ; Aries et al , ; Leni et al , ), as well as other metabolic pathway inhibitors (Hermanova et al , ), showed direct anti‐cancer cytotoxicity or synergised with other anti‐leukaemia agents in childhood leukaemia. Therefore, we performed microarray‐based analyses to screen glycolysis/glycogenesis‐related gene expression in childhood B‐ALL and found that SLC2A5 was overexpressed in Ph+ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Glycolysis is critical in childhood ALL. Several pre‐clinical studies showed that aerobic glycolysis inhibitors (Hulleman et al , ; Aries et al , ; Leni et al , ), as well as other metabolic pathway inhibitors (Hermanova et al , ), showed direct anti‐cancer cytotoxicity or synergised with other anti‐leukaemia agents in childhood leukaemia. Therefore, we performed microarray‐based analyses to screen glycolysis/glycogenesis‐related gene expression in childhood B‐ALL and found that SLC2A5 was overexpressed in Ph+ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the antiapoptotic protein Mcl-1 was shown to be required for cell survival in BCR-ABL+ leukemia [11], and to play a role in the survival of ALL [12, 13], CML [15], hematopoietic stem cells [35], T-lymphocytes [36], and plasma cells [37]. Herein, we demonstrate that Mcl-1 plays a crucial role in the survival of BCR-ABL+ ALL cells undergoing energy/ER-stress.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of glycolysis using a glucose analog, 2-deoxyglucose (2-DG) has already been shown to re-sensitize acute lymphoblastic leukemia (ALL) cells to prednisolone therapy (Hulleman et al, 2009). The combination of 2-DG and an MCL1 anti-apoptotic protein inhibitor is proved to be synergistic in overcoming prednisolone resistance in ALL cells (Aries et al, 2013). Our recent study of AML cell lines revealed enhanced expression of genes relating to both glycolysis and the TCA cycle (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%